2008
DOI: 10.1088/0004-637x/690/1/837
|View full text |Cite
|
Sign up to set email alerts
|

CIRCUMSTELLAR12C/13C ISOTOPE RATIOS FROM MILLIMETER OBSERVATIONS OF CN AND CO: MIXING IN CARBON- AND OXYGEN-RICH STARS

Abstract: A survey of the 12 C/ 13 C ratio toward circumstellar envelopes has been conducted at millimeter wavelengths using the facilities of the Arizona Radio Observatory (ARO). The ratios were obtained for a sample of local C-and O-rich asymptotic giant branch and supergiant stars from observations of the 12 C and 13 C isotopologues of CO and CN, respectively. The J = 1 → 0 transitions of both molecules were observed at λ = 3 mm using the ARO 12 m telescope, while the J = 2 → 1 lines of the two species were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
67
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 62 publications
(73 reference statements)
10
67
4
Order By: Relevance
“…This suggests a 12 C/ 13 C isotopic ratio that is higher than what is found in M-type AGB stars (Knapp & Chang 1985;Milam et al 2009) and more in line with those derived for carbon stars (Knapp & Chang 1985;Milam et al 2009). However, we note here that Hinkle et al (1976) derive a 12 CO/ 13 CO-ratio of 25 ± 7 from CO vibrational lines (i.e., from lines originating in the stellar atmosphere) and that Milam et al (2009) Recently, Menten et al (2010) presented HIFI observations of the ortho-NH 3 J K = 1 0 → 0 0 transition for a sample of four oxygen-rich evolved stars. They report relatively high NH 3 abundances in the range from 2 × 10 −7 to 3 × 10 −6 .…”
Section: Isotope Ratiossupporting
confidence: 81%
“…This suggests a 12 C/ 13 C isotopic ratio that is higher than what is found in M-type AGB stars (Knapp & Chang 1985;Milam et al 2009) and more in line with those derived for carbon stars (Knapp & Chang 1985;Milam et al 2009). However, we note here that Hinkle et al (1976) derive a 12 CO/ 13 CO-ratio of 25 ± 7 from CO vibrational lines (i.e., from lines originating in the stellar atmosphere) and that Milam et al (2009) Recently, Menten et al (2010) presented HIFI observations of the ortho-NH 3 J K = 1 0 → 0 0 transition for a sample of four oxygen-rich evolved stars. They report relatively high NH 3 abundances in the range from 2 × 10 −7 to 3 × 10 −6 .…”
Section: Isotope Ratiossupporting
confidence: 81%
“…The spread on 12 C/ 13 C for the other stars in the sample is quite large and we do not see any clear differences in the first-order estimates of 12 C/ 13 C when considering the different types of stars in the sample. Milam et al (2009) found 12 C/ 13 C ∼ 13 for NML Cyg and 12 C/ 13 C ∼ 14 for IRC +10420, while for VY CMa they derived a much higher value between 25 and 46. We find similar ratios with a first order estimate for VY CMa of 14.8, and values of 8.7 and 8.1 for NML Cyg and IRC +10420, respectively.…”
Section: C/ 13 C Isotope Abundance Ratiomentioning
confidence: 93%
“…They analysed the multiple components for 12 C/ 13 C separately, resulting in three different values for VY CMa (46, 33 and 25) and 2 values for V Hya (71 and 72). Milam et al (2009) claim a ±30% uncertainty on their 12 C/ 13 C-values. Olofsson et al (1993) and Oudmaijer et al (2009) suggest that the acceleration of winds around C-rich stars is more efficient than that of winds around O-rich stars because of differences in dust absorption properties.…”
Section: C/ 13 C Isotope Abundance Ratiomentioning
confidence: 98%
See 2 more Smart Citations